Psychological Aspects of Congenital Hypogonadotropic Hypogonadism - Dwyer, Andrew A.; Smith, Neil; Quinton, Richard (Frontiers in Endocrinology, 2019)
Congenital hypogonadotropic hypogonadism/Kallmann syndrome (CHH/KS) is a rare, treatable form of infertility. Like other rare disease patients, individuals with CHH/KS frequently experience feelings of isolation, shame and alienation. Unlike many rare diseases, CHH/KS is not life threatening and effective treatments are available. Nevertheless, it remains a profoundly life-altering condition with psychosocial distress on a par with untreatable or life-limiting disease. Patients with CHH/KS frequently express lasting adverse psychological, emotional, social and psychosexual effects resulting from disrupted puberty. They also frequently experience a ‘diagnostic odyssey’, characterized by distressing and convoluted medical referral pathways, lack-of-information, misinformation, and sometimes-incorrect diagnoses. Unnecessary delays in diagnosis and treatment-initiation can significantly contribute to poor body image and self-esteem. Such experiences can erode confidence and trust in medical professionals as well as undermine long-term adherence to treatment - with negative sequelae on health and wellbeing. This review provides a summary of the psychological aspects of CHH/KS and outlines an approach to comprehensive care that spans medical management as well as appropriate attention, care and referrals to peer-to-peer support and mental health services to ameliorate the psychological aspects of CHH/KS.